Winter mixed-layer development in the central Irminger Sea : the effect of strong, intermittent wind events - Våge, Kjetil (Massachusetts Institute of Technology, 2006)
Thesis (S.M.)--Joint Program in Physical Oceanography (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2006. Includes bibliographical references (p. 81-86). The impact of the Greenland tip jet on the wintertime mixed-layer of the southwest Irminger Sea is investigated using in-situ moored profiler data and a variety of atmospheric data sets. The mixed-layer was observed to reach 400 m in the spring of 2003, and 300 m in the spring of 2004. Both of these winters were mild and characterized by a low North Atlantic Oscillation (NAO) index. All of the storms that were advected through the region were tracked, and the tip jet events that occurred throughout the two winters were identified. Composite images of the tip jets elucidated the conditions during which tip jets were likely to take place, which led to an objective method of determining tip jet occurrences by taking into account the large-scale pressure gradients. Output from a trajectory model indicates that the air parcels entering a tip jet accelerate and descend as they are deflected around southern Greenland. A heat flux timeseries for the mooring site was constructed that includes the enhancing influence of the tip jet events. This was used to drive a one-dimensional mixed-layer model, which was able to reproduce the observed mixed-layer deepening in both winters. All of the highest heat flux events took place during tip jets, and removal of the tip jets from the heat flux timeseries demonstrated their importance in driving convection east of Greenland. (cont.) The deeper mixed-layer of the first winter was in large part due to a higher number of robust tip jet events, which in turn was caused by a greater number of storms passing northeast of southern Greenland. This interannual change in storm tracks was attributable to a difference in upper level steering currents. Application of the mixed-layer model to the winter of 1994-1995, during a period ...